An Exploration of the Practice of Buying and Selling Mobile Legends Diamonds Based on Sharia Economic Law - Jemani; Daud; Khoiratun Nisak, Sayida; Kurniawan; Sunarti, Zeni; Kartika Devi, Erwina; Okva Marwendi, Reza (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to examine the practice of purchasing Mobile Legends diamonds at Toko Samsul Muin Jaya from the perspective of Sharia economic law. Employing a descriptive qualitative approach through a single case study design, this research provides an in-depth analysis of digital transaction mechanisms within a rural context. Data were collected through observation, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña model. The findings reveal that the transaction practices are conducted informally, lacking contractual clarity, transparency of the transaction object, and adequate consumer protection. Although the shop is trusted by the local community due to its speed and affordable pricing, the practices still involve elements of gharar (uncertainty) and do not fully comply with Sharia standards. The novelty of this research lies in its direct exploration of digital buying and selling practices in rural areas, which remain underexplored in contemporary Islamic economic law literature. The findings underscore the importance of digital-based Sharia economic literacy education and the active role of religious leaders and regulators in guiding communities toward fair, transparent, and Sharia-compliant digital economic practices